Racial Ideology or Racial Ignorance? An Alternative Theory of Racial Cognition. (June 2020) - Mueller, Jennifer C.
Directing attention to racial ignorance as a core dimension of racialized social systems, this article advances a process-focused Theory of Racial Ignorance (TRI), grounded in Critical Race Theory and the philosophical construct white ignorance. TRI embodies five tenets—epistemology of ignorance, ignorance as ends-based technology, corporate white agency, centrality of praxis, and interest convergence. TRI's tenets explain how racial ignorance reinforces white domination, attending to mechanisms of white knowledge evasion and resistance that facilitate racial reproduction—in everyday life, through institutions, and across societies more broadly. I illustrate TRI's assets by comparison to an extant theory of racial cognition—color-blind theory (CBT). I argue TRI generates returns by shifting from racial ideology to racial ignorance, and from era-defined structures to ongoing historical processes; and demonstrate TRI's unique capacity to explain and predict changes in dominant logics, supporting more strategic resistance.